Essentials of management information systems : managing the digital firm - Laudon, Kenneth C., 1944-; Laudon, Jane Price (Ph. D.). (Upper Saddle River, NJ : Prentice Hall, 2005)
This text contains a wealth of pedagogical features to facilitate student comprehension, which aid in reviewing and reinforcing key concepts, as well as promoting problem-solving skills.
Managing the digital firm -- Information systems in the enterprise -- Information systems, organizations, management, and strategy -- The digital firm: electronic business and electronic commerce -- Ethical and social issues in the digital firm -- Hardware and software in the enterprise -- Managing data resources -- Telecommunications, networks, and wireless computing -- The internet: information technology infrastructure for the digital firm -- Enterprise applications and business process integration -- Managing knowledge in the digital firm -- Enhancing management decision making for the digital firm -- Redesigning the organization with information systems -- Understanding the business value of systems and managing change -- Information system security and control.
Includes bibliographical references (p. 597-616) and index.
Keywords: Management information systems